EKSISTENSI BADAN PENYELESAIAN SENGKETA KONSUMEN SEBAGAI LEMBAGA QUASI PERADILAN - Pebri Anwar; Ari Widiarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
The existence of quasi-judicial institution as a part of judicial power. Article 24 subsection (3) of the constitution of the Republic of Indonesia 1945 and the law number 48/2009 about judicial power admitting quasi yudicial institutionshas judicial powers. The purpose of establshing BPSK is to protec consumer and producer by designing consumer protection system that contain legal certainty. The problems that the decision of BPSK has characteristic final and binding however it can be carried out to the district court and the decision cannot be executed directly or realized. For maximalize exercising of the quasi-judicial institutions are needed legal policy for supporting functional-constitusional relations between BPSK and Supreme Court as top judicial power organization.